PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING CHIPS UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATERI STRUKTUR ATOM DI KELAS X MIA SMA NEGERI 12 PEKANBARU - Rahmi, Marhaini; Erviyenni, Erviyenni; M Noer, Asmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the increase in student learning achievement by applying cooperative learning models talking chips type to Atomic Structure material in class X MIA SMAN 12 Pekanbaru. The form of this study uses the Pretest-Posttest Design Randomized Control Group. The sample consisted of class X MIA 5 as the experimental class and X MIA 6 as the control class which was randomly selected after the normality test and homogeneity test. The experimental class is a class that applies the cooperative learning model of talking chips. The data analysis technique uses test techniques. Testing the hypothesis using the T test with α = 0.05 obtained by Tcount> Ttable (1.98> 1.66). Based on hypothesis testing it was concluded that the application of cooperative learning models talking chips type can improve student learning achievement in the Atomic Structure material in class X MIA SMAN 12 Pekanbaru..Key Words: Atomic structure, learning achievement, cooperative learning modeltype talking chips